Building psychological resilience in military personnel theory and practice (American Psychological Association, 2013)
"Efforts to exclude the less resilient from serving in the military represent a narrow and flawed understanding of what resilience is and the potential for resilience building to enhance the strength of a military. We must focus on the strengths that every individual possesses rather than the weaknesses. We must focus on team building and leadership and avoid adopting an individualistic and elitist model that harkens back to the medieval mind-set. The field of military resilience holds the promise to fundamentally transform the military in ways that are just now being imagined; to limit this potential by focusing efforts on identifying and excluding those we deem less resilient will certainly retard this potential. The contents of this book rightly focus on achieving these goals by addressing two major areas: understanding the nature and determinants of resilience in military settings, and describing methods and techniques for building resilience. Although it can be argued that resilience is a somewhat nebulous construct that has many definitions, the present volume tackles this problem by attempting to inform an improved definition for the betterment of both military personnel and their families. As advances in military resilience are realized, we must never forget that military service is fundamentally about preparing for and fighting and winning our nation's wars, which is achieved through teamwork and leadership"--Foreword. (PsycINFO Database Record (c) 2013 APA, all rights reserved)